2019
DOI: 10.17776/csj.519415
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Optical Properties of Indium Selenide (InSe) Thin Films Deposited on Glass and GaSe Single Crystal Substrates by SILAR Method

Abstract: Structural, morphological and optical properties of undoped and boron doped Indium Selenide (InSe) thin films grown on glass and layered Gallium Selenide (GaSe) single crystal substrates with SILAR method have been investigated by XRD, AFM and UV-Vis spectrophotometer techniques. XRD measurements showed that the crystal structure of InSe thin films grown on glass substrates were hexagonal P61 γ-In2Se3 with lattice parameters a=7.1286 Å, c=19.382 Å and z=6 while the InSe thin films grew as hexagonal P63/mmc InS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The deposition of Ag 2 S (silver sulfide) films took place on glass slides by using a complexing agent (ammonia (NH 3 )) at 40 • C [17]. Films showed monoclinic phases and preferred orientations corresponding to the (120) plane. Improvements in crystallinity and the red shift in absorption edge could be observed when the deposition cycle increased from 20 to 50 cycles.…”
Section: Silver Sulfide Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The deposition of Ag 2 S (silver sulfide) films took place on glass slides by using a complexing agent (ammonia (NH 3 )) at 40 • C [17]. Films showed monoclinic phases and preferred orientations corresponding to the (120) plane. Improvements in crystallinity and the red shift in absorption edge could be observed when the deposition cycle increased from 20 to 50 cycles.…”
Section: Silver Sulfide Filmsmentioning
confidence: 99%
“…The indium selenide (InSe) films were deposited onto glass substrates (75 cycles) and gallium selenide (GaSe) single crystal substrates (50 cycles), respectively, by using indium (III) sulfate (In 2 (SO 4 ) 3 ) and Na 2 SeSO 3 solution [120]. The XRD studies revealed the hexagonal phase and lattice parameters, such as a = 7.128 Å, c = 19.382 Å, z = 6 for the films grown on glass.…”
Section: Indium Selenide Filmsmentioning
confidence: 99%
See 1 more Smart Citation